Konstruksi Nalar Hukum Fatwa Pemboikotan Produk Terafiliasi Israel di Indonesia - Innayah, Firly; Bashori, Akmal (Program Studi Hukum Ekonomi Syariah, 2024)
This article focuses on the issue of the Indonesian Ulema Council’s (MUI) fatwa regarding boycotting products affiliated with Israel, with a focus on the epistemological construction of MUI fatwa No. 83 of 2023. To answer this problem, this article uses the theory of ijtihād. Considering that the type of research is literature with the data source being MUI fatwa 83 2023, then it is analyzed using descriptive analysis. From the results of this research, it can be concluded that the fatwa is a form of Indonesia’s support for the Palestinian struggle, one of which is an appeal to boycott products affiliated with Israel. In deciding this Fatwa, the MUI used the reasoning of Bayānī, Ta’līlī, and Iṣtislaḥī.